Evaluasi Penerimaan PBB Paska UU PDRD (UU No 28 Tahun 2009)(Studi Kasus di Wilayah Kabupaten Boyolali) - Putri, Istikhomah Kusuma, Dr. Erma Setiawati, Ak., M.M (2016)
This research is motivated by the issuance of law No. 28 year 2009 on Regional taxes and retributions, The Central Goverment devolved the management of land and building tax (PBB) of Rural and Urban sector to The Local Government. The purpose of this study to evaluate the growth rate and the level of effectiveness of land and building tax receipts before and after the issuance of Law No. 28 year 2009 made by The Revenue Department of Finance and Asset Management to the local tax revenue of Boyolali district. Data used in this research is secondary data obtained from The Revenue Department of Finance and Asset Management in the form of data revenue of land and building tax from 2011 until 2014. The research used is descriptive quantitative method. The result of this research concludes that the growth rate of land and building tax growth was not stable from year to year with an average growth of 8,61% per year. While, the level of effectiviness of land and building tax receipts (PBB) from 2011 untill 2014 has not yet reached the target with an average of 75,20% per year with less effective criteria.